The Role of Design Management in Product Design Innovations - Renáta ŠEVČÍKOVÁ (Communications of International Proceedings, 2021)
Although design is increasingly recognized as an important marketing tool, design management is still an ignored component of its success. Design management is playing an increasingly important role in enabling the company to better reflect on market needs and adapt to the customer. When design management is part of a company's management processes, design will have a more significant impact on the company's economic performance and help ensure a competitive advantage in the market. The aim of the paper is to analyse the five factors of design management and their impact on the use of design in product innovation. We selected the field of machinery & equipment industry as one of the most important sectors of the Slovak economy and compared the results with foreign studies. Primary data were obtained using a standardized query method. Descriptive statistical and mathematical methods were used to process the results of the questionnaire. The results suggest that design management plays an important role in the use of design as a product innovation. Good design is not just a coincidence, it is the result of a controlled process. Lack of skills in design management is a barrier to more widespread implementation and integration of design into companies.
Keywords: Design Management; Design; Product Innovation; Company's Economic Performance